(untitled) (Konturen, 2010)
This essay attempts to compare and contrast the different conceptions of the human subject in Claude Lévi-Strauss and Jacques Lacan, with specific reference to the notions of art and the act. For this occasion I will draw on my reading of structuralism, developed elsewhere, as a “logic of the aesthetic perception of the social.” Structuralism apparently distances itself from the act, but it presupposes the act as a foundation. Psychoanalysis takes the act as its point of departure and seeks its art. In each case, the human subject is conceived differently. Nonetheless, the exercise appended to this essay proposes a space in which these two approaches can perhaps encounter each other on the common ground of structure.